Forensic analysis of counterfeit psychotropic drugs - Klara Dégardin; Aurélie Guillemain; Alexandra Feng; Christian Saladin; Stéphanie Paratte; Raphaël Zurbach; Tobias Mohn (Talanta Open, 2024)
Medicine counterfeiting is a worldwide problem affecting all therapeutic areas. The analysis of such products is sometimes a scientific challenge, since their chemical composition is unknown and might be very different from the one of the original product. While some counterfeited drug products are quite easy to detect, others are close in composition with the genuine products. The health consequences of counterfeit medicines are appalling since these products can contain the =rong chemical composition, impurities or toxic compounds, and be manufactured and stored in dreadful conditions that do not even respect the basic hygienic conditions. Providing reliable analytical tools is therefore necessary for an efficient fight against the phenomenon. In this study, the analysis of counterfeits of psychotropic drugs presenting a rare closeness in composition to the genuine drugs will be described. It will be exposed how the choice of reliable analytical strategy and tools is decisive for the correct authentication of such pharmaceuticals. The results of classical methods like High-Performance Liquid Chromatography (HPLC) will be presented. Then the contribution of vibrational spectroscopy and imaging tools, including spectral imaging and Near infrared (NIR) spectroscopy, and spectral imaging, will be described, as well as Gas Chromatography coupled with Mass Spectrometry (GC–MS), 1H Nuclear Magnetic Resonance (NMR), 3D microscopy as support for the physical analysis, and finally X-ray fluorescence spectroscopy (XRF) as an elemental analysis technology. The results of the forensic analysis will also reveal analytical links between the counterfeit cases, providing useful information for law enforcement investigations.